Evaluation of Flood Hazard Potency in Jakarta based on Multi-criteria Analysis - RR Mashita Fauzia Hannum; I Putu Santikayasa; Bambang Dwi Dasanto (Agromet, 2022)
The frequency of flood events in Indonesia has increased since 1990, especially in the capital city of Jakarta. Flood events have affected socio-economic activities, and have threaten community health in flood prone areas. Although many efforts have been performed to reduced flood impacts, research on flood hazard remains a research challenge. This study aims to map level of flood hazard in Jakarta and to determine the most affected factors that cause flood. First, we defined factors that influence flood, and combined an analytical hierarchy process (AHP) to determine their weighted values and GIS approach to determine their score values. The combination of weight and score value determined the flood hazard index (FHI). The sensitivity analysis and validation then were applied to determine the robustness of the approaches. Our results show that the most influenced factors determining flood hazard were rainfall intensity, land use, and slope, whereas geology is the less factor. Based on the sensitivity analysis and FHI validation, our approaches were able to represent 59% flood disaster in Jakarta. The pattern of FHI value was high in north areas and low in south areas. The findings indicated that north areas are more flood prone than south areas. Further, this research contributes to the improved approach of flood mitigation in Jakarta